2022
DOI: 10.1155/2022/7607470
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Study of Lactobacillus rhamnosus (PTCC 1637) as a New Therapeutic Candidate in Esophageal Cancer

Abstract: Statement of Novelty. Esophageal cancer is one of the most common types of cancer globally. Nowadays, Lactobacilli with probiotic potency is a preventing factor in cancer and many diseases. The anti-tumor properties of these bacteria have been indicated in various studies. Objective. This study is aimed at investigating the effect of probiotic Lactobacillus rhamnosus on esophageal cancer in vivo and in vitro. Methods and Results. In this study, the cytotoxicity effects of L. rhamnosus supernatant and whole-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…LGG and LR PMs. In contrast to our study, when cells were treated with LR, the increased expression of BAX and casp3 genes in HT29 cells and a decrease in Wnt signaling pathway gene expression has been observed, which impacts cell proliferation and differentiation in Kyse30 cells [24,25]. Furthermore, a study…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…LGG and LR PMs. In contrast to our study, when cells were treated with LR, the increased expression of BAX and casp3 genes in HT29 cells and a decrease in Wnt signaling pathway gene expression has been observed, which impacts cell proliferation and differentiation in Kyse30 cells [24,25]. Furthermore, a study…”
Section: Discussioncontrasting
confidence: 97%
“…The observed reduction in Jurkat cell viability after treatment with LGG and LR PMs is in line with previous research reporting the anticancer potential of probiotics and their derived products, specifically in leukemia [21][22][23]. Our results are consistent with other studies reporting the anticancer effects of probiotic bacteria and their metabolites on various cancer cell lines, including colon, breast, and esophageal cancer [22,24,25]. It should also be noted that the cytotoxic impacts of Lactobacillus strains on cancerous cells are not limited to their live forms.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that the communication between probiotic intestinal bacteria and their mammalian hosts involves immune control by LAB MVs 27 . The significant effects of whole-cell components and supernatants of probiotic lactobacilli in preventing, inhibiting, and treating various cancers, such as lung, colon, breast, colorectal, stomach, and others, are also taken into consideration 31 , 32 . However, to the best of our current knowledge, there have been no studies on the anticancer properties of MVs isolated from probiotic Lentilactobacillus buchneri.…”
Section: Introductionmentioning
confidence: 99%
“…Another probiotic Lactobacillus rhamnosus (PTCC 1637) may also be promising in case of esophageal cancer, what has been confirmed in Hashemi-Khah et al. study ( Hashemi-Khah et al., 2022 ). Despite the fact that overall Lactobacillus spp.…”
Section: Consideration Of Probiotics As Supportive Treatment Of Esoph...mentioning
confidence: 68%